Study of Genetic Diversity of grain yield-associated traits in Iranian and Exotic Safflower (Carthamus tinctorius) Germplasm - M. M. Majidi; R. Dehghan Kouhestani; R. Malekinejad; G. Saeidi (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
Safflower (Carthamus tinctorius L.) is cultivated in a wide range of geographical conditions in the world from Africa to Europe, India and China. Previous studies have shown that diversity in indigenous Iranian germplasm is limited for some traits therefore germplasm collections from other origins need to be considered. An experiment was conducted to evaluate agronomic and morphological traits of 100 Iranian and exotic safflower genotypes during 2011- 2012 at the Research Farm of Isfahan University of Technology, Isfahan, Iran, using a simple lattice design of 10 × 10. The results of analysis of variance showed that the differences among genotypes were highly significant (p < 0.01) for days to flowering, seed yield, plant height, number of heads per plant, number of seeds per head, 1000-seed weight, oil content and harvest index, indicating high variability in the studied germplasm. The highest and lowest heritabilities were observed for 1000-seed weight and seed yield, respectively, indicating that indirect improving for seed yield would be more beneficial. Genetic and phenotypic correlation coefficients showed that number of heads per plant, number of seeds per head and harvest index had significantly positive correlations with seed yield. The results of stepwise regression and path analysis showed that number of heads per plant, number of seeds per head and 1000-seed weight are the most important components of seed yield, among which, number of heads per plant had the greatest direct positive effect on seed yield. These traits could be used as criteria for indirect selection in safflower breeding programs. Factor analysis recognized three factors which explained 72.56 percent of total variations. These factors were defined as phenological, physiological source and efficiency factors. Cluster analysis based on the agronomic and morphological traits grouped the genotypes into three clusters. Iranian accessions were clearly discriminated from other genotypes and allocated in the group three. In conclusion, the results indicated that there was a broad genetic diversity among Iranian and foreign germplasm which can be exploited in breeding programs.